The Effect of Short-Term Use of Cold Spray on Strength and Ankle Joint Position Sense in Professional Wrestlers - Hamidreza Naserpour; Heydar Sadeghi (Biyumikānīk-i varzishī, 2017)
Objective: The aim of this study was to investigate the effect of a short period of cryotherapy on strength and ankle position sense in professional wrestlers. Methods: In this semi experimental study, fourteen Professional wrestlers (age 24/2+3/5 years old, and weight 74/1+19/2 kg), all of whom had at least five years training experience with provincial and national championships participated in this study. Manual Muscle Tester was used to measure the strength of dorsi and plantar flexor muscle before and after cryotherapy that was simultaneously applied on medial-lateral of the ankle, with distance 30 cm. Meanwhile, performance accuracy of the ankle joint was assessed via Electrogoniometer that measures the active and passive regeneration error of ten and twenty angles of dorsi and plantar flexion respectively, before and after cold application. Shapiro-Wilk test was used to check the normality distribution, and a paired samples t- test was run to compare variables with a significant level of (p≤0.05).